The Central Role of Tuan Guru in the 19th Century Social Revolution Movement in Lombok - Ahmad Tohri; Zulkarnain Zulkarnain; Huldiya Syamsiar; Lalu M. Istiqlal; Abdul Rasyad; Bambang Eka Saputra (UIN Sunan Gunung Djati, 2023)
This research discusses the central role of Tuan Guru in the social revolution movement of Sasak people against colonialism in Lombok island in the 19th century. This research was combined research (blended research) in qualitative research and used social movement theory as a collective action that offers change or resistance to bring about new life. The Sasak social revolution movement was motivated by the prolonged commonality of the fate suffered by the annexation of local and global colonialism-imperialism. The central role of Tuan Guru in the social revolution movement of Sasak people in the 19th century in Lombok began with the unification of social stratification between the ruling aristocratic group and the ruling non-aristocratic group, bound by a specific fraternity, the fraternal brotherhood (shufi brotherhood). The religious fraternity which transformed into tarekat communities in Lombok, especially Tarekat Naqsyabandiyah Congregation and Qadiriyah wa Naqsyabandiyah reconstructed themselves into a religio-political system in moving social revolution against colonialism which gave birth to rebellions and tyranny which contradicted Islamic doctrine in general and the teaching of tarekat in a religious way special.